Formação continuada de professores na rede de ensino de São Luis: uma análise a partir do Pacto Nacional pela Alfabetização na Idade Certa PNAIC/UFMA-SEMED - SALAZAR, Jerry Wendell Rocha (2018)
The context of Teacher Training in Brazil has been marked by different training trends, plans, goals and high investments in teacher training, but few changes have been significant. In view of this scenario, in the present research we aim to analyze the conception / conceptions of PNAIC Teachers Continued Formation within the Municipal Education Network of São Luís. In this sense, it was necessary to identify in the PNAIC guiding documents the underlying pedagogical conceptions to pedagogical practices, as well as to understand the material conditions of the teaching work that made possible the production of the pedagogical practices of the PNAIC. As a methodological foundation, we adopted the qualitative approach, through bibliographical, documentary and field research. Our approach finds theoretical home in Historical-Dialectical Materialism, having the Marxist referential as a compass. In this way, the empirical data collection, the semi-structured interviews with the actors of the research were based on Kosik (1976), Gourde (2012), Gadotti (2010), Frigotto (2010), Tanuri 2000). In order to achieve this goal, research was conducted on the relationships and interactions of social and political spheres related to teacher training in the PNAIC, considering Duarte (2003), Silva (2001), Santos (2010, 2014), Freitas (1992,1995) , Vituriano (2008); Prazeres (2007); Nóvoa (1995); Saviani (2005) among others. Marx (1978, 1982, 2008), Marx and Engels (2007). The results of the research indicate that the process of implementation of the PNAIC since its inception in 2013 has undergone restructuring, advances and systemic setbacks. The research also identified that the perspective of continuing education present in the PNAIC is based on the studies of Philippe Perrenoud (1993), Maurice Tardif (2002) and Kenneth Zeichner (1998), Schön (2000) of teachers based on Practical Rationality as opposed to that based on Critical (or Praxis) Rationality. Despite the limits observed in the training practices analyzed, the teachers participating in this research considered them an important tool for their professional development.